Inspeksi Material menggunakan Mikro-Radiografi Sinar-X Digital melalui Pengukuran Densitas: Prasetyo Listiaji, Gede Bayu Suparta - Prasetyo Listiaji Prasetyo Listiaji; Gede Bayu Suparta Gede Bayu Suparta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
X-ray digital radiography is a non-destructive digital imaging technique that utilizes X-ray radiation that penetrates material objects. This technique can be used to analyze the internal structure and composition of objects properly. Research has been carried out on material inspection using X-ray digital micro-radiography that has been developed in the Physics Department, FMIPA UGM. Material samples inspected were 2B and HB pencils. All samples were irradiated by X-rays with a tube voltage of 30 kV and a filament current of 20 mA. Several images were taken for each sample, then averaged and calculated the grayscale value (intensity). Density was calculated based on variations in the intensity difference that passes through the pencil. The radiographic image showed that the internal structure of the pencil object, were wood and graphite can be distinguished. The measurement results were obtained for HB pencils, the value of the graphite density of HB pencils was (2,52 ± 0,02) g/cm3 and graphite density of 2B pencils was (1,84 ± 0,02) g/cm3. The results of density different between HB graphite and 2B graphite indicate that X-ray radiography techniques can be an alternative for material inspection purposes and density measurement.